Dynamics of the Screw Conveyor for Transportation and Cleaning of Fiber Material - Anvar Djuraev, Kozimjon Yuldashev (International Journal of Advanced Science and Technology, 2020)
The article presents the construction diagram and the principle of operation of conveyor with zigzag profile screw. Based on the solution of the problem of system dynamics, taking into account the dynamic-mechanical characteristics of the motor, inertial, elastic-dissipative parameters, as well as technological loads from the transported and cleaned cotton lint, regularities of the working element are obtained, and basic parameters of the conveyor are justified. Based on production comparative tests of the recommended conveyor, the efficiency of its use in production is justified.